A Result Base Various Approaches of Data Security in Cloud Computing - Singh, Gurbachan; Bansal, Khushboo (International Journal of Computer Sciences and Engineering, 2025)
In this paper we are studied cloud computing techniques. The Homomorphic property of various cryptosystems can be used to create secure voting systems, collision-resistant hash functions, and private information retrieval schemes and enable widespread use of cloud computing by ensuring the confidentiality of processed data.